Influencia de la comunicación organizacional de flujo cruzado en las relaciones laborales individuales de los colaboradores de nexus technology s.a.c. 2014 - Julca Julca, Deysi Rosa (2014)
The theory that guides this study is the Systems Theory, giving us a holistic, integrated and comprehensive perspective of a set of elements that help us understand the dynamics of organizations, where what matters are the relationships from them emerge as a company we have many items that are daily interacting with each other, building relationships in the workplace, which is called labor relations. The contribution and importance of this study is put as a topic of discussion and analysis, organizational communication crossflow of view in terms of employees as part of everyday life in the development of labor relations, thus contributing to the knowledge of the profession in the field of intervention of companies and organizations, while contributing to the work of the social workers in the area of social welfare not only as part of the Human Resources area, but also in the implementation of strategies in social Management our role as intermediary in the partner - employee relationship. Sample was considered as 65 employees, distributed among the three managers, Administration and Finance, Trade and Logistics who have allowed the knowledge of their valuations and their thinking on the topic treated in their workplace. The results to concluding that the influence of crossflow communication is positive since it is manifested in the personal satisfaction to feel valued at work in a motivating environment; and personal fulfillment through satisfying their need for self-fulfillment and personal growth. Therefore it is important that social work from the humanistic perspective contribute to the welfare of the employee by improving labor, social, health, personal and family issues through appropriate internal and external efforts to obtain the balance of interests of the company for a better service to the company and society.